Selected Abstracts of the 8th International Congress of UENPS; Bucharest (Romania); October 3rd-5th 2018; Session "Updates in neonatal resuscitation and stabilization" - - (Hygeia Press di Corridori Marinella, 2018)
Selected Abstracts of the 8th International Congress of UENPS; Bucharest (Romania); October 3rd-5th 2018; Session "Updates in neonatal resuscitation and stabilization" ABS 1. BLOOD GAS DIFFERENCES BETWEEN THE UMBILICAL ARTERY AND VEIN IN TERM AND PRETERM NEWBORNS • S. Perrone, M.L. Tataranno, G. De Bernardo, D. Trevisanuto, D. Sordino, M. Riccitelli, G. Buonocore ABS 2. IS UMBILICAL CORD BLOOD LACTATE MEASUREMENT A RELIABLE PROGNOSTIC TOOL FOR POSTNATAL OUTCOME? • M. Simon, M. Cucerea, L. Suciu, Zs. Gáll, R. Sánta ABS 3. SHOULD WE TAKE GESTATIONAL AGE INTO CONSIDERATION WHEN ASSESSING AN ECG? • M.S. Pimenta, N. Samesima, C.A. Pastore, V.L.J. Krebs, W.B. Carvalho ABS 4. THE ROLE OF SERUM NTpBNP LEVELS IN DETECTING HEMODYNAMICALLY SIGNIFICANT PDA IN PRETERM NEONATES • S. Ercin, D. Arman, G. Karatekin ABS 5. THERAPEUTIC HYPOTHERMIA IN NEONATAL HYPOXIC ISCHEMIC ENCEPHALOPATHY IN A PORTUGUESE TERTIARY LEVEL CARE NEONATAL UNIT: 6 YEARS EXPERIENCE • S. Moeda, F. Pinto, G. Cassiano, C. Matos, T. Tomé ABS 6. USE OF A CLINICAL SCORE TO PREDICT OUTCOME IMMEDIATELY AFTER NEONATAL TRANSPORTATION • O. Boantă, C. Zgârcea, R. Dumitra, M.L. Ognean ABS 7. KEEPING READY FOR RESUS: IMPROVING NEONATAL RESUSCITATION EQUIPMENT AVAILABILITY IN THE DELIVERY ROOM • C.M. Moore, H. Wall, M. Cronin, A.E. Curley ABS 8. USE OF INOTROPES AND OUTCOMES IN PRETERM INFANTS • G.A. Alchamat, I.A. Maguid, T.W. Agina, S.P. Patil, C.P.H. Ibrahim ABS 9. WHERE ARE WE NOW WITH NEONATAL RESUSCITATION • J. Bukeyeneza, C. Bélanger Bishinga, T. Perreault ABS 10. ASSESSMENT OF TRANSFUSION PRACTICES IN A NORTHERN AFRICA COUNTRY: A STUDY OF 111 CASES • A. Bouraoui, A. Badri, A. Ben Hamad, M. Charfi, Ch. Regaieg, I. Ben Amor, G. Daoud, R. Regaieg, N. Hamida, A. Ben Thabet, A. Gargouri